A Robust Electrochemical Sensor Based on Butterfly‐shaped Silver Nanostructure for Concurrent Quantification of Heavy Metals in Water Samples. Issue 2 (1st July 2022) - Naseri, Maryam; Mohammadniaei, Mohsen; Ghosh, Koustuv; Sarkar, Subrata; Sankar, Ravi; Mukherjee, Subhankar; Pal, Souvik; Ansari Dezfouli, Ehsan; Halder, Arnab; Qiao, Jixin; Bhattacharyya, Nabarun; Sun, Yi
Abstract: Heavy metals in drinking water have become a severe threat to human health. Detection of heavy metals has been achieved by electrochemical sensors that are modified with complex nanocomposites; however, reproducibility of these sensors is still a big challenge when applied in commercial settings. Here, a simple, very robust, and sensitive electrochemical sensor based on a screen‐printed carbon electrode modified with butterfly‐shaped silver nanostructure (AgNS/SPCE) has been developed for the concurrent determination of cadmium (II), lead (II), copper (II), and mercury (II) in water samples. The electrochemical behavior of the modified electrodes was investigated using cyclic voltammetry and differential pulse anodic stripping voltammetry. The AgNS/SPCE showed distinct peak potentials and a significant increase in the peak currents for all heavy metals, attributed to the high electrical conductivity and electrocatalytic activity of the synthesized butterfly‐shaped AgNS. Moreover, the excellent stability and sensitivity towards simultaneous quantification of heavy metals have been obtained with detection limits of 0.4 ppb, 2.5 ppb, 7.3 ppb, and 0.7 ppb for Cd (II), Pb (II), Cu (II), and Hg (II), respectively. Besides, the constructed sensor was successfully applied to simultaneously quantify target heavy metals in spiked water samples. Owing to excellent sensitivity, high robustness, affordability, and fast response, the presented electrochemical sensor could be incorporated into a portable and miniaturized potentiostat device, making it a promising method for on‐site water analysis. Abstract : An electrochemical sensor has been developed based on screen‐printed carbon electrode modified with butterfly‐shaped silver nanostructure for the concurrent detection of Cd (II), Pb (II), Cu (II), and Hg (II) in water with the excellent stability and high sensitivity. The synthesized butterfly‐shaped AgNS provided four distinguish signals for target heavy metals and enhanced the electrochemical signals.